2005
DOI: 10.1016/j.jvs.2004.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Use of short PTFE segments (<6 cm) compares favorably with pure autologous repair in failing or thrombosed native arteriovenous fistulas

Abstract: Short (<6 cm) interposition PTFE segments used for the revision of failing or failed AVFs compare favorably to purely native repair and do not alter the autologous behavior of the initial access. These short PTFE revisions resulted in satisfactory midterm primary patency without further consumption of the venous capital by harvesting segments of vein from other locations and without compromising more proximal access sites. This practice is recommended and is justified as part of an aggressive access salvage po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
38
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 31 publications
5
38
0
1
Order By: Relevance
“…Having shown a three-fold adjusted relative risk for restenosis after PTA by comparison with surgery, our study confirms the results of previous noncomparative studies that reported higher primary patency rates in surgical series than after dilation in failing forearm AVF (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)25,26,28). Moreover, the unadjusted 1-yr primary patency rates in our series (91 Ϯ 6% for surgery and 54 Ϯ 8% for PTA) compare favorably with the literature, which reports rates of 64 to 88% after preemptive surgery (12,19,25,26) and 16 to 79% after endovascular procedures (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Having shown a three-fold adjusted relative risk for restenosis after PTA by comparison with surgery, our study confirms the results of previous noncomparative studies that reported higher primary patency rates in surgical series than after dilation in failing forearm AVF (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)25,26,28). Moreover, the unadjusted 1-yr primary patency rates in our series (91 Ϯ 6% for surgery and 54 Ϯ 8% for PTA) compare favorably with the literature, which reports rates of 64 to 88% after preemptive surgery (12,19,25,26) and 16 to 79% after endovascular procedures (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the unadjusted 1-yr primary patency rates in our series (91 Ϯ 6% for surgery and 54 Ϯ 8% for PTA) compare favorably with the literature, which reports rates of 64 to 88% after preemptive surgery (12,19,25,26) and 16 to 79% after endovascular procedures (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In addition, restenosis rates after the two surgical techniques were similar in our study, failing to support the concern of any higher complication rates' being associated with the PTFE interposition graft (24).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Where outcomes for a single operative technique have been described, case numbers have generally been small. 9,[12][13][14][15] Larger, more detailed, analyses of outcomes after specific techniques enable more meaningful comparisons between surgical procedures and between surgical and endovascular therapies. The aims of this study were therefore to examine the outcomes and complications of operative salvage of RCAVFs by the NEO technique.…”
mentioning
confidence: 99%